Peran Australia Mewujudkan Komitmen Paris Agreement untuk Adaptasi Iklim di Kiribati - Munthe, Rouli Triana; Baiti, Ainun Nur; Callista, Aurora Shafa; Tambunan, Putri Marlen (Jurnal Ilmiah Hubungan Internasional Fajar, 2025)
This journal is written using a descriptive qualitative research method that uses a case study approach, by examining the policies carried out, and how the form of bilateral cooperation carried out by Australia to support Kiribati in dealing with the effects of Climate Change. The results of this journal will show how the assistance provided by Australia can play an important role as a regional actor through building climate resilience infrastructure, supporting the “Migration with Dignity” policy with the aim of preparing Kiribati people for possible migration due to climate change, and increasing human resource capacity. Australia's assistance includes building coastal resilience, skills training, strengthening the education sector, and providing basic services that are adaptive to climate change. This support not only helps Kiribati improve its adaptive capacity, but also strengthens both countries' commitment to implementing the Paris Agreement on Climate Adaptation. The journal attests to Australia's significant role in helping Kiribati meet the challenges of climate change and safeguarding its ecosystems and the well-being of its people. Keywords: Paris Agreement, Climate Change, Australian Aid